Dagnostic and prognostic importance of clinical-immunological correlations of postpartum period after abdominal delivery - R. A. Belovolova; I. A. Evdokimova; E. V. Belovolova; I. V. Smirnova (Медицинский вестник Юга России, 2010)
Purpose: Research of clinical-immunological characteristics, detection of diagnostic and prognostic significance in pre- and postsurgical periods and immunocorrection potential.Materials and Methods: 59 pregnant women with gestation period of 38-40 weeks and on the 6-7-th day after labor. Clinical-immunological characteristics, US- factors of postnatal involution of uterus were estimated. The estimation of immune state include research of humoral and cellular components of immune system.Results: Pregnant women who belong to a risk group after C-section more often have complications in postnatal subinvolution of uterus with dysfunction of immune system on the 6-7-th day after labor. Usage of superlymph in complex therapy is accompanied with a certain clinical effect and normalization of immunogram indices.